The Humoral Immune Response Induced by Snake Venom Toxins - Dias da Silva, Wilmar; V. Tambourgi, Denise (Inflammation & Allergy-Drug Targets (Discontinued), 2011)
This review summarizes the key contributions to our knowledge regarding the immune response induced by snake venom toxins, focusing particularly on the production of antibodies and their venom-neutralizing effects. We cover the past and present state of the art of anti-snake venom production, followed by an overview of the venomous snakes and their venoms. The toxic properties of relevant snake venom toxins are approached in some details, with particular emphasis on the molecular domains responsible for binding to cells or plasma components in victims. The interactions of these domains are also reviewed, particularly the putatively relevant epitopes, along with the immune system and the resulting antibodies. We also review trials aimed at reducing the quantities of non-relevant antibodies in the antivenoms by substituting whole venoms with purified toxins to immunize animals, or the immunogenicity of the heterologous antivenom antibodies by humanizing their molecules.
Keywords: antibody